2022
DOI: 10.3389/phrs.2022.1604796
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators in Access to Diabetes, Hypertension, and Dyslipidemia Medicines: A Scoping Review

Abstract: Objective: Identify barriers and facilitators in access to medicines for diabetes, hypertension, and dyslipidemia, considering patient, health provider, and health system perspectives.Methods: Scoping review based on Joanna Briggs methodology. The search considered PubMed, Cochrane Library, CINAHL, Academic Search Ultimate, Web of Science, SciELO Citation Index, and grey literature. Two researchers conducted screening and eligibility phases. Data were thematically analyzed.Results: The review included 219 docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 199 publications
2
7
0
Order By: Relevance
“…The existence of unfavorable waiting areas compounded the unpleasant experiences faced by the patients at their respective facilities therefore minimizing the possibility of complete engagement of patients in various aspects of their care and predicting both compliance and utilization of the facility services. Consistent findings of unfavourable facility environments have been elucidated by other relevant studies [ 15 , 21 , 37 , 38 ]. A systematic and qualitative meta-synthesis study revealed significant service delivery network problems, particularly among low-middle-income countries where most of the diabetes health services are provided by public clinics established within hospitals in district and regional capitals [ 39 ].…”
Section: Discussionsupporting
confidence: 83%
“…The existence of unfavorable waiting areas compounded the unpleasant experiences faced by the patients at their respective facilities therefore minimizing the possibility of complete engagement of patients in various aspects of their care and predicting both compliance and utilization of the facility services. Consistent findings of unfavourable facility environments have been elucidated by other relevant studies [ 15 , 21 , 37 , 38 ]. A systematic and qualitative meta-synthesis study revealed significant service delivery network problems, particularly among low-middle-income countries where most of the diabetes health services are provided by public clinics established within hospitals in district and regional capitals [ 39 ].…”
Section: Discussionsupporting
confidence: 83%
“…The presentation of the results is divided into three subsections: 1) Description of the participants; 2) General perceptions on access to health, and the barriers and facilitators depending on the dimensions of access (3–5); and 3) the differences between the perceptions of the FONASA and ISAPRE beneficiaries regarding access to medicines.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, access to medicines implies their availability at a reasonable distance, their acceptance by patients and physicians and the real possibility of financing. These dimensions, as well as multiple barriers and facilitators associated with each of them, were also identified globally by a scope review on medications associated with three chronic conditions of high prevalence (5), finding that the most reported dimension, in countries of all regions and income levels, is affordability, and among the most relevant barriers, the availability of medications, long distances, cost, professional support and cultural aspects (5). Despite the therapeutic importance of pharmaceutical drugs, the lack of access to essential medicines, defined as those that meet the priority health care needs of the 5 population, is one of the most serious public health problems globally, affecting one third of the world's population, with consequences for loss of life and deterioration of health (6).…”
Section: Introductionmentioning
confidence: 99%
“…Equitable access to medicines for hypertension and diabetes is crucial for reducing the burden of NCD41 42; providing medicines at the PHC level has shown a practical approach to reducing blood pressure-related deaths 43. Moreover, the Sustainable Development Goal for universal health coverage requires access to safe, adequate quality and affordable medicine 44.…”
Section: Discussionmentioning
confidence: 99%